FAKTOR-FAKTOR YANG MEMPENGARUHI TINDAK PIDANA KORUPSI APARAT PEMERINTAH DAERAH - Laily Rahmawati; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the factors that influence the corruption of local government officials. The population in this study were Malang city government employees. Samples used. The technique used in sampling is purposive sampling technique, the sample chosen was 139 respondents. Data was taken using the questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS version 16 software (Product Statistics and Solution Services version 16). The test data used is the simultaneous hypothesis test (f), determination coefficient (R2), and partial hypothesis test (t). The results of the study indicate that simultaneously the independent variables significantly influence the dependent variable. Based on the test results of the coefficient of determination, the adjusted R value is 87.9% while the remaining 12.1% is influenced by other variables not included in this study. Based on the results of partial tests of individual behavior variables have a positive effect on criminal acts of corruption, government organizations have a negative influence on corruption, per law has a positive effect on criminal acts of corruption, supervision has a positive effect on corruption.Keywords: individual behavior, government organization, by law, supervision